Implementation of the Modernization Policy of the Main Equipment of the National Maritime Defense Weapon System : Study on Minimum Essential Force Phase II 2015-2019 - Armadani, Gracia Sarah; Kosandi, Meidi (International Journal of Social Service and Research, 2024)
This study explores the implementation of the Navy's main weapon system modernization policy in the context of meeting the Minimum Essential Forces (MEF) Phase II for the 2015-2019 period, whose main focus is to overcome threats to national security. The purpose of the study is to explain the implementation process of the Navy's defense equipment modernization policy related to MEF and analyze policy factors that affect the results of its implementation. Using defense policy data and theory, the study identified obstacles such as budget constraints, differences in understanding between policy actors, less optimal supervision, and the role of the defense industry that has not been maximized. Document evaluation, interviews, and monitoring by defense experts show that the main constraint is not just related to limited resources, but rather to the imbalance of political will of policy actors. Consistency of implementation, commitment to transparency, accountability, and improvement of resource capabilities through priority scale and empowerment of the defense industry require the support of political will. The contribution of this research includes the development of political science, particularly in the context of defense and security politics. The results can be a reference for future researchers who are interested in understanding the issue of defense equipment modernization. The successful implementation of this policy is expected to have a significant impact on national defense and national security policies, with the support of political will identified as the main key to minimizing conflicts of interest and increasing the effectiveness of MEF implementation, maintaining national security.